2013
DOI: 10.1097/mph.0b013e31827e8dbd
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Venous Sinus Thrombosis in Pediatric Cancer Patients

Abstract: Cerebral venous sinus thrombosis (CVST) is an uncommon but recognized complication of treatment for leukemia. Our goal was to determine the long-term neurocognitive outcomes in childhood cancer survivors who had CVST during therapy. Nine patients were identified from an institutional database. All had experienced CVST in the setting of L-asparaginase therapy in combination with other chemotherapeutic agents. Four patients completed neuropsychological evaluation. Their neurological examinations were normal. Neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 10 publications
(13 reference statements)
0
12
0
Order By: Relevance
“…(Von der Weid,2001; Langer et al,2002; Hill et al,2004; Spiegler et al,2006; Mahone et al,2007; Aukema et al,2009; Kadan-Lottick et al,2009; Kadan-Lottick et al,2010; Robinson et al,2010; Daams et al,2012; Krawczuk-Rybak et al,2012; Edelmann et al,2013; Genschaft et al,2013; Krull et al,2013; Lewis et al,2013; Ross et al,2013; Schuitema et al,2013; Edelmann et al,2014; Elalfy et al,2014) There were only 4 longitudinal studies that evaluated survivors’ neurocognitive changes from active treatment to post-treatment survivorship phase. (Kingma et al,2001; Harila et al,2009; Halsey et al,2011; Lewis et al,2013) Most studies focused on a pure sample of survivors who received chemotherapy-only treatment protocols while others included separate populations of ALL survivors who received CRT(Kingma et al,2001; Von der Weid,2001; Langer et al,2002; Spiegler et al,2006; Harila et al,2009; Kadan-Lottick et al,2010; Halsey et al,2011; Krull et al,2011; Daams et al,2012; Krull et al,2013; Schuitema et al,2013; Edelmann et al,2014) or patients of other cancer types.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(Von der Weid,2001; Langer et al,2002; Hill et al,2004; Spiegler et al,2006; Mahone et al,2007; Aukema et al,2009; Kadan-Lottick et al,2009; Kadan-Lottick et al,2010; Robinson et al,2010; Daams et al,2012; Krawczuk-Rybak et al,2012; Edelmann et al,2013; Genschaft et al,2013; Krull et al,2013; Lewis et al,2013; Ross et al,2013; Schuitema et al,2013; Edelmann et al,2014; Elalfy et al,2014) There were only 4 longitudinal studies that evaluated survivors’ neurocognitive changes from active treatment to post-treatment survivorship phase. (Kingma et al,2001; Harila et al,2009; Halsey et al,2011; Lewis et al,2013) Most studies focused on a pure sample of survivors who received chemotherapy-only treatment protocols while others included separate populations of ALL survivors who received CRT(Kingma et al,2001; Von der Weid,2001; Langer et al,2002; Spiegler et al,2006; Harila et al,2009; Kadan-Lottick et al,2010; Halsey et al,2011; Krull et al,2011; Daams et al,2012; Krull et al,2013; Schuitema et al,2013; Edelmann et al,2014) or patients of other cancer types.…”
Section: Resultsmentioning
confidence: 99%
“…(Aukema et al,2009; Kadan-Lottick et al,2010) The majority of the included studies had sample sizes between 10 to 50 subjects,(Kingma et al,2001; Langer et al,2002; Hill et al,2004; Mahone et al,2007; Aukema et al,2009; Harila et al,2009; Daams et al,2012; Krawczuk-Rybak et al,2012; Edelmann et al,2013; Genschaft et al,2013; Schuitema et al,2013; Edelmann et al,2014) with the exception of 4 studies with a larger cohort of more than 100 subjects(Von der Weid,2001; Kadan-Lottick et al,2010; Halsey et al,2011; Krull et al,2013) and 3 studies with less than 10 subjects. (Lewis et al,2012; Lewis et al,2013; Ross et al,2013) Most the studies reported survivors’ mean duration of time since diagnosis, which ranged between 5 and 22 years. Eighteen studies included a population of non-cancer controls or a normative healthy sample for comparative purposes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All patients had previously been treated with l-asparaginase. 19 Each patient's CSVT was treated with lowmolecular-weight heparin. Of the 4 patients who were available for long-term follow-up, all had normal or nearnormal neuropsychological outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, Ross et al published the results of their study about long-term neurological outcomes after a median follow-up of 8 years (range 5-10 years). 34 Nine of 200 pediatric patients developed sinovenous thrombosis after treatment with asparaginase for ALL or NHL. Four patients underwent neurological examination and neuropsychological testing.…”
Section: Morbidity and Mortalitymentioning
confidence: 99%